Identification and in Vitro Digestion Characteristics of Bound Ferulic Acid in Feruloylated Arabinoxylan from Jizi439 Black Wheat Bran - LI Yiyun, LIU Zhengjia, WANG Guozhen, CHANG Xianhui, DING Wenping, CHEN Xi (Shipin Kexue)
Feruloylated arabinoxylan (F-AX) was extracted from black wheat bran by either of two methods: ultrasonic-assisted enzymatic extraction or alkaline extraction as control. The content and linkage of bound ferulic acid in the extract were investigated, and its antioxidant and in vitro digestive properties were studied. Our results showed that the enzymatic extract possessed lower relative molecular mass in a wider range when compared with the alkaline extract. They differed in monosaccharide composition and glycosidic linkage. The amount of ferulic acid in the enzymatic extract, (13.11 ± 0.19) μg/mg, was significantly higher than that of the alkaline extract, (0.05 ± 0.01) μg/mg. During the in vitro digestion of the enzymatic extract, the release of ferulic acid was very low at various digestion stages (oral: (0.06 ± 0.01) μg/mg, gastric: (0.60 ± 0.02) μg/mg, intestinal: (0.14 ± 0.01) μg/mg). In addition, the enzymatic extract possessed higher antioxidant activity than the alkaline extract. Our results provide a theoretical basis to fully preserve ferulic acid and its bioactivity during F-AX extraction from wheat bran, to explore its physiological effects, and to unleash the nutritional value of grain resources.